Parameter Estimation of Neuroachfet Circuit using Advanced Algorithm for Application in Neurology - Rashmi Deka (Journal of Global Pharma Technology, 2017)
In 1952, Hodgkin-Huxley have developed an electronic circuit describing the biophysical nature of a neuron. Acetylcholine field effect transistor (AchFET) has been developed in this paper for detection of Acetylcholine (neurotransmitter) and then the AchFET is used in an electronic circuit to reproduce neuronal signals. AchFET is an enzyme field effect transistor (ENFET) fabricated by immobilizing acetylcholine in the gate terminal for proper detection of Acetylcholine. The neuron signals obtained from the circuit using AchFET is named as NEUROAchFET (Neuro Acetylcholine field effect transistor). In the next step, estimation of parameters is done using Firefly Algorithm for signals obtained from the NEURO AchFET. There are various parameters related to neuron signals described in this paper and estimation are done for NEUROAchFET circuit to validate the circuit. Firefly algorithm is used since it is an advanced algorithm and proved to be better than other metaheuristic algorithms. Keywords: Neuron, Acetlycholine, Hodgkin-Huxley, NeuroAchFET, Firefly Algorithm.